Relationship Between Body Composition and Physical Performance by Sex in Professional Basketball Players - Herrera-Valenzuela, T; Cid-Calfucura, I (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study aimed to identify the relationship between body composition (fat-free mass and body fat percentage) and physical performance (countermovement jump, CMJ; throwing ball; maximal isometric handgrip strength, MIHS dominant and non-dominant hands; 10-m and 20-m sprints with and without ball) in Chilean professional basketball players. Its secondary aim was to analyze if there were differences in body composition and physical performance according to sex. This was a cross-sectional study that analyzed 23 professional basketball players with a mean age of 24.0 ± 4.92 years, distributed among male professional basketball players (male professional BPs, n = 12) and female professional basketball players (female professional BPs, n = 14). The main results indicate the correlation presented significant relationships between fat-free mass with CMJ (r = 0.760; p < 0.0001; ES = 1.43), MIHS dominant hand (r = 0.783; p < 0.0001; ES = 1.50) and MIHS non-dominant hand (r = 0.805; p < 0.0001; ES = 1.85), throwing ball (r = 0.586; p = 0.001; ES = 0.56), 10 m sprint with ball (r = −0.510; p = 0.007; ES = 0.35), and 20 m sprint with ball (r = −0.143; p = 0.046; ES = 0.16). As did body fat percentage with CMJ (r = −0.647; p = 0.000; ES = 0.56), throwing the ball (r = −0.657; p = 0.000; ES = 0.58), MIHS dominant hand (r = −0.745; p < 0.0001; ES = 1.17), and MIHS non-dominant hand (r = −0.820; p < 0.0001; ES = 1.50). In conclusion, body composition is related to physical performance in professional basketball players. Meanwhile, male professional BPs had better body composition and physical performance than female professional BPs. © 2024 by the authors.